Executable Business Process Modeling - Bogoslovskaya, Natalya Valentinovna; Brzhezovskii, Aleksandr Viktorovich (Razvitie obrazovaniâ (Online), 2020)
As noted in the explanatory note to the «Information Systems Specialist» professional standard, the success of implementing information systems is largely determined by the accuracy of their adaptation to the business processes of the customer organization. Today, BPMN notation is often used as a tool for extracting requirements for information systems. BPMN provides executable semantics that make it possible not only to draw up a detailed specification of a business process, but also to model it with numerical estimates. The aims of this study are to choose tools for teaching students from the number provided by BPMN notation: descriptive, analytical and executable, which allow to implement the third level of modeling; to define a methodology for teaching business modeling, including the ability to execute business processes in the universal BPMN runtimes and as an add-on on the configuration of the information system. The following methods have been used: comparative analysis and testing of the functionality provided for the development of business processes in the Bizagi and 1C: Enterprise tool environments, including the creation of the data and presentation layers necessary for BPMN execution. As a result, the main stages of business modeling are formulated, a functional comparison of tools for working at the following stages has been carried out: development of a business process model; development of a data layer that supports the execution of the process; mapping data to process tasks – forms of user tasks; programming business rules governing the process; execution of a business process by user-performer. The peculiarity of 1C: Enterprise is that the business process is essentially a superstructure over the layers of data and representations of the finished configuration of a process-oriented information system. The authors believe that both the first and the second approach deserve attention in terms of the educational process at the university for students of 09.03.02 «Information systems and technologies» specialty.